Proposals for improving the teaching of social studies in three vocational schools in Cebu City - Reyes, Romeo R. 1943- (1976)
This paper is structured into four parts: the discussion of the background and significance of this study, related studies and literature, prevailing social studies practices in three vocational schools in Cebu City, and the summary and recommendations for improving the teaching of social studies in the the three vocational schools in Cebu City.